Sharia Finance Literacy, Ethics, and Media Impact on Gen Z Spending - Fiqrotinnisa; Nur Kholis (At-Thullab : Jurnal Mahasiswa Studi Islam, 2026)
This study aims to analyze and compare the influence of Islamic financial literacy, Islamic consumption ethics, peers, and social media on the consumptive behavior of Gen Z students in the Islamic Economics Study Program at the Islamic University of Indonesia (UII) and Muhammadiyah University of Yogyakarta (UMY). This study employs a quantitative approach using multiple linear regression analysis and the Mann-Whitney test to determine differences in consumer behavior between the two groups of respondents. Data were collected from 169 students via an online questionnaire. The results indicate that all four variables simultaneously have a significant influence on the consumer behavior of students at both universities. Partially, Islamic financial literacy and Islamic consumption ethics have a significant influence on UII students but not on UMY students. Conversely, the variables of peers and social media have a significant influence on students at both universities. The Mann-Whitney test indicated that there were no significant differences in consumer behavior between UII and UMY students, except for the social media variable, which showed a higher influence on UII students. These findings suggest that Gen Z students' consumer behavior is not only influenced by internal values and knowledge but also by external factors such as social environment and digital exposure. This study contributes theoretically by integrating financial and social variables into the Islamic economic approach and practically by providing insights for Islamic higher education institutions in designing financial literacy and Islamic consumption ethics curricula relevant to Gen Z characteristics